The ecological impact on the distribution of Pangolins in Deng-Deng National Park, Eastern Region, Cameroon - Melle Ekane Maurice; Esong lionel Ebong; Nkwatoh Athanasius Fuashi; Ichu Ichu Godwill; Amos Fang Zeh (Global Journal of Ecology - Peertechz Publications, 2019)
One of the major impediments to studying wild pangolins has been the difficulty in locating them. In many areas where biodiversity surveys have been conducted, no pangolins were recorded, despite extensive nocturnal searches. The main objective of this survey was to assess the role of ecological factors on the distribution of pangolins in deng-deng national park. The research data collection method used for this study constituted the laying of fifteen 2-kilometre transects in the study area. The collection of relevant data such as pangolin feeding-material signs, burrows, trails, foot-prints together with ecological parameters such as vegetation type, weather conditions, landscape and forest canopy type. The survey revealed that weather conditions and Pangolin-sign encounter rate were significant, χ2 = 6.125df=9 P<0.05. Moreover, a significant association was found between canopy-types and the animal species encounter rate, χ2 = 27.006 df=8 P<0.05. There was also a significant link between the age of pangolin-sign and the forest-type, χ2 = 29.995 df=30 P<0.05. The recent pangolin-sign recorded the highest encounter rate frequency 42.67%, while the fresh-signs encounter rate recorded 34.67% in the survey. The gentle and steep slopes both recorded an animal occurrence frequency of 41.3%, as compared to the very steep slope landscape 17.3%. This study has revealed that the pangolin species in deng-deng national park have an ecological distribution influence. Hence, the protection of these pangolin species would be much enhanced by the proper conservation and national park management strategies put in place by the Cameroon government.